IHSG dan Tantangan Ekonomi Global: Moderasi Suku Bunga The Fed dalam Pengaruh Ekonomi Makro (2019-2023) - Prista, Alexchandra Nurfadila; Ika Prajawati, Maretha (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study aims to examine the impact of macroeconomic factors, including the Rupiah exchange rate, interest rates, inflation, and global oil prices, on the Jakarta Composite Index (IHSG), with the Fed's interest rate serving as a moderating variable. A quantitative method is employed using secondary data from the 2019-2023 period. The results indicate that domestic interest rates and global oil prices significantly affect the IHSG, while the Rupiah exchange rate and inflation do not. Moreover, the Fed's interest rate moderates the effects of domestic interest rates and global oil prices on the IHSG but does not moderate the influence of the Rupiah exchange rate and inflation. These findings suggest that the impact of macroeconomic factors on the IHSG in Indonesia does not always align with the predictions of Signaling Theory and the Mundell- Fleming Model.